Новые даты к абсолютной хронологии эпохи энеолита степного Причерноморья (предварительная информация) - Рассамакин, Ю.Я. (Археологический альманах, 2009)
The new radiocarbon dates of the Eneolithic graves from Black Sea steppe mounds are presenting in this paper. The dates from human bones samples made in the Kyiv Radiocarbon Laboratory cover the time span from 5480±100 BP until 5430±80 BP for the Early Eneolithic, 5230±60 BP for so called hiatus, from 4980±70 BP until 4720±80 BP for the Middle Eneolithic and after 4548±28 BP for the Late Eneolithic. Author analyse the new dates: the first in context of the stratigraphy of mounds, the second in context of the Trypillia culture chronology. Author use also the existing radiocarbon dates for Eneolithic graves for comparative analysis of new dates.